2015
DOI: 10.7726/ajhmt.2015.1003
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Flow-pattern Formation in a Cylindrical Cell with Partially Immersed Heating Element

Abstract: A non-Boussinesq weakly compressible-low numerical model is used to study the temperature and luid velocity distribution in a cylindrical tank with a heating element partially immersed in a temperature dependent luid. This con iguration is commonly found in immersion heaters and electrolytic cells where the heating element does not extend along the entire axial length of the cylindrical vessel. A very particular vortex pattern arises inside the cell which strati ies the domain dividing it into two regions of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It was shown that the Boussinesq approximation could not adequately simulate natural convection flow for a high temperature difference in the domain. Sharma et al [27] studied the flow and thermal maps in a cylindrical tank where a heater was partially immersed inside it, and implemented temperature-dependent properties for the working fluid (Non-Boussinesq approach). The study found that with an increase in the aspect-ratio of the tank, the Nusselt number at the surface of the heater and at the surface of cylindrical tank would increase and decrease, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the Boussinesq approximation could not adequately simulate natural convection flow for a high temperature difference in the domain. Sharma et al [27] studied the flow and thermal maps in a cylindrical tank where a heater was partially immersed inside it, and implemented temperature-dependent properties for the working fluid (Non-Boussinesq approach). The study found that with an increase in the aspect-ratio of the tank, the Nusselt number at the surface of the heater and at the surface of cylindrical tank would increase and decrease, respectively.…”
Section: Introductionmentioning
confidence: 99%